Intellettuali e uomini di regime nell'Italia fascista - Barucci, Piero; Bini, Piero; Conigliello, Lucilla (Studi e saggi, 2019)
Intellettuali e uomini di regime nell'Italia fascista. This volume collects nine essays on political, economic and legal culture in Italy during fascism. The reconstruction of prominent personalities of the regime, such as Giuseppe Volpi di Misurata and Alberto Beneduce, are accompanied by studies analysing the at times critical, at times organic relationship between the regime and a series of reputed intellectuals, such as Vilfredo Pareto, Giuseppe Maranini, Jacopo Mazzei and Francesco A. Répaci. A chapter is dedicated to Edoardo Moroni, Minister of Agriculture during the Italian Social Republic, who after the war emigrated to Argentina, where he made a significant contribution to the agrarian reform of the country. This volume also includes two essays outside of the biographical trend: the first focuses on the theme of unemployment during Fascism, while the second presents the main aspects of the Urban Planning Act of 1942.